2011
DOI: 10.1039/c0cp02386h
|View full text |Cite
|
Sign up to set email alerts
|

Collision-induced gas-phase reactions of perhalogenated closo-dodecaborate clusters – a comparative study

Abstract: The gas phase reactivity of perhalogenated closo-dodecaborate clusters [B(12)X(12)](2-) (X = F, Cl, Br, I) with N-tetraalkylated ammonium counter ions was investigated by electrospray ionization ion trap mass spectrometry (ESI-IT-MS). Collisions with the background gases introduced a broad variety of gas phase reactions. This study represents the first experimental approach to a new class of boron-rich boron clusters that are not accessible in the condensed phase. The anionic ion pair [B(12)X(12) + N(C(n)H(2n+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
87
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(101 citation statements)
references
References 60 publications
(37 reference statements)
12
87
0
2
Order By: Relevance
“…For full details, see ref. 8. Bottom: Icosahedral and planar structures, showing the B atom numbering used.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For full details, see ref. 8. Bottom: Icosahedral and planar structures, showing the B atom numbering used.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we prepared B 12 ions with any number of iodine substituents from 12 to one, by fragmenting B 12 I 12 2− through electrospray ionization–ion‐trap mass spectrometry (ESI‐MS) 8. At the end of the fragmentation path, B 12 I 1 − loses a neutral B 12 unit, thus leaving behind I − (Figures 1 and 2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…B12X12 2− ) is often studied by the electrospray ionization mass spectrometry (ESI-MS). 18 The ions produced by ESI-MS often can capture internal energy in the range of 100 -200 kJ mol −1 , which corresponds to temperature of several thousands Kelvin. Therefore, we computed the Gibbs free energies, ΔG, for both open-and close-B12X7 − at 300, 1500, and 5000 K, through the harmonic approximations for the minimum structures on the potential energy surface at 0 K. The Gibbs free energies were computed by ΔG = Gico -Gope = ΔU + RT -TΔS (U is the internal energy, T is the temperature, R is the gas constant and S is the entropy), and the data are given in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, a complete series of partly iodinated B12In x− (with n = 1 to 12, x = 1 or 2) was successfully generated in the gas-phase and was studied by mass spectroscopy. 18 Together with theoretical calculations, it was shown that the most stable structures for n ≥ 8 remain the icosahedral B12 cages. The planar structures are preferred for n ≤ 4.…”
Section: Introductionmentioning
confidence: 99%